Commercial victimisation survey, 2023 (UK Data Service, 2025)
This data collection is the 2023 iteration of the Commercial Victimisation Survey (CVS), a survey of the extent of crime and crime related issues experienced by business premises in England and Wales. It provides additional detail on the extent of crime, to be used alongside the other main sources of information on crime. These are the Crime Survey for England and Wales (CSEW) (formerly the British Crime Survey), which covers crimes against private individuals and households, and the Police Recorded Crime statistics, which cover crimes reported to the police. The CVS was previously run as a standalone survey in 1994 and again in 2002. The CVS was then run as an annual publication from 2012 onwards. A break occurred from 2019 to 2021 where CVS underwent a re-design following a consultation. A standalone CVS was run in 2021, covering only the Wholesale and Retail sector, to provide insights on the effects of the COVID-19 pandemic. From 2022 onwards, the coverage of the survey has included all commercial business premises. The 2023 CVS aims to estimate the extent and nature of crime affecting all commercial business premises in England and Wales. The data includes the prevalence and frequency of crime affecting business premises in England and Wales: as well as impacts on premises, crime prevention measures taken up by premises, experiences of the police, and attitudes to the police.